PRIMARY VAGINAL MALIGNANT MELANOMA: A REPORT OF TWO CASES AND REVIEW OF THE LITERATURE (Vietnam Journal of Community Medicine, 2026)
Background: Primary vaginal melanoma is a rare malignancy, accounting for only 0.3-0.8% of all melanomas and less than 3% of primary vaginal malignancies. Due to the rich vascular and lymphatic network of the vagina, the disease is highly aggressive, prone to early metastasis, and associated with an extremely poor prognosis, with a low 5-year survival rate ranging from 8.4-25%. Herein, we report two clinical cases of primary vaginal melanoma diagnosed and treated at Vietnam National Cancer Hospital, campus 1.Case presentation: Case 1: a 52-year-old female patient presented with a 2 × 3 cm mass on the posterior vaginal wall. She underwent a laparoscopic radical hysterectomy, bilateral salpingo-oophorectomy, total vaginectomy, and bilateral pelvic lymphadenectomy. Immunohistochemistry results confirmed malignant melanoma with a Breslow depth of 4 mm, along with negative surgical margins and regional lymph nodes. Currently, the patient remains stable after 12 months of regular follow-up. Case 2: a 38-year-old female patient presented with a 38 × 39 mm tumor located in the middle third of the vagina. She underwent an open total hysterectomy, en bloc total vaginectomy, bilateral pelvic and inguinal lymphadenectomy, followed by pelvic reconstruction using a greater omental flap. Histopathological evaluation revealed a Breslow depth of approximately 30 mm and the presence of melanoma in situ at the vaginal margin. The patient is currently receiving adjuvant immunotherapy with Pembrolizumab (200 mg every 3 weeks) and is in her 15th cycle. At present, both patients are clinically stable with no evidence of local recurrence or distant metastasis.Conclusion: Surgical resection of the primary tumor remains the cornerstone of treatment for primary vaginal melanoma. However, for high-risk cases, the integration of adjuvant immune checkpoint inhibitors plays a crucial role in controlling micrometastasis and improving disease-free survival.
Keywords: Vaginal cancer, vaginal melanoma, melanoma.